City of ashes - Clare, Cassandra (New York : Walker Books, 2015)
Still pursuing a cure for her mother's enchantment, Clary uses all her powers and ingenuity to get into Idris, the forbidden country of the secretive Shadowhunters, and to its capital, the City of Glass, where with the help of a newfound friend, Sebastian, she uncovers important truths about her family's past that will not only help save her mother but all those that she holds most dear.
Keywords: Supernatural -- Fiction; Demonology -- Fiction; Magic -- Fiction; Vampires -- Fiction; New York (N.Y.) -- Fiction